Abiotic Nitrous Oxide Production From Sediments and Brine of Don Juan Pond, Wright Valley Antarctica, at Mars Analog Temperatures (−40°C). Issue 3 (1st February 2022) - Schutte, Charles A.; Samarkin, Vladimir A.; Bowles, Marshall W.; Peters, Brian; Casciotti, Karen L.; Madigan, Michael T.; Joye, Samantha B.
Abstract: The presence of biogenic gases such as oxygen, methane, and nitrous oxide (N2 O) in the atmospheres of extraterrestrial bodies has been postulated as a biosignature of life. Abiotic N2 O production was documented recently in Don Juan Pond (DJP), Antarctica, a cold, hypersaline Mars analog environment. Here we quantify the temperature‐driven kinetics of abiotic N2 O production and combine this with stable isotope labeling to demonstrate that N2 O is produced from DJP sediment and brine at Mars‐analog temperatures down to at least −40°C. Further, we show that at any given temperature, N2 O production is controlled by the availability of reduced Fe‐bearing minerals rather than nitrate. We conclude that abiotic N2 O production is possible on Mars and on other extraterrestrial bodies and exoplanets. Thus, the presence of atmospheric N2 O on these bodies should not be taken by itself as an indicator of microbial life. Plain Language Summary: The search for extraterrestrial life has long captured our collective imagination, but it is hindered by the difficulty of actually visiting extraterrestrial planets, moons, asteroids, etc. to search for life. An alternative strategy is to remotely analyze the atmospheres of these planets to look for trace gases that exist in Earth's atmosphere because they are produced by living organisms across the biosphere. One such gas is nitrous oxide. We visited a remote, extremely cold, and salty desert pond in the Dry Valleys of Antarctica, an environment that is considered to be among the most similar to Mars that can be found on Earth. There, we studied the production of nitrous oxide in the absence of microbial life. We show that this gas is produced through the interaction between rock and chemical precursors in water at extremely cold temperatures (−40°C) that are similar to those observed on Mars. Because nitrous oxide can be produced in the absence of life, we conclude that its presence in the atmosphere of another planet or planetary moon does not necessarily indicate the presence of life on that object. Key Points: Abiotic nitrous oxide production occurs at temperatures down to −40°C in Mars‐analog environment (DJP), Antarctica Across temperatures, abiotic nitrous oxide production is controlled by the availability of reduced iron rather than nitrate availability The presence of atmospheric nitrous oxide on an extraterrestrial body should not by itself be considered evidence of life